2014
DOI: 10.1007/s00382-013-2040-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of distinct intraseasonal oscillation in summer monsoon rainfall over the Meghalaya–Bangladesh–western Myanmar region: covariability between the tropics and mid-latitudes

Abstract: Detailed spatiotemporal structures for the submonthly-scale (7-25 days) intraseasonal oscillation (ISO) in summer monsoon rainfall and atmospheric circulation were investigated in South Asia using high-quality rainfall and reanalysis datasets. The Meghalaya-Bangladesh-coast of the western Myanmar (MBWM) region is the predominant area of submonthly-scale ISO in the Asian monsoon regions. The distinct rainfall ISO is caused by a remarkable alternation of low-level zonal wind between westerly and easterly flows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 50 publications
6
61
0
Order By: Relevance
“…Fujinami et al (2011) found that the rainfall spectrum in Bangladesh has a pronounced peak at about 14 days, while no statistically significant peak appears within the 30-60-day period. They also reported that the interannual variability of the total summer monsoon rainfall over Bangladesh is correlated significantly with the 7-25-day rainfall variance, suggesting that the QBW controls the interannual variability of the total seasonal rainfall in the country.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Fujinami et al (2011) found that the rainfall spectrum in Bangladesh has a pronounced peak at about 14 days, while no statistically significant peak appears within the 30-60-day period. They also reported that the interannual variability of the total summer monsoon rainfall over Bangladesh is correlated significantly with the 7-25-day rainfall variance, suggesting that the QBW controls the interannual variability of the total seasonal rainfall in the country.…”
Section: Introductionmentioning
confidence: 93%
“…These two ISO modes have differing spatiotemporal structures. The BSISO mode exhibits northward propagation of convection and circulation anomalies from the equatorial Indian Ocean (e.g., Yasunari 1981;Murakami et al 1984;KemballCook and Wang 2001;Lawrence and Webster 2002;Jiang et al 2004;Wang et al 2006), whereas the QBW mode is characterized by westward propagation of convection and circulation anomalies from the western Pacific (e.g., Krishnamurti and Ardanuy 1980;Chen and Chen 1993;Yokoi and Satomura 2005;Hoyos and Webster 2007;Kikuchi and Wang 2009;Fujinami et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations